Thesaurus on rice - Daywin, Liannie K.; Zamora, Milagros C.; Mabbayad, Basilio B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1980)
This THESAURUS ON RICE consisting of the Categorized Listing and Alphabetical Listing attempts to control the vocabulary of rice terms. With the steadily increasing volume of rice literature, there is a need for vocabulary control to consolidate and interrelate these various terms to guide the processors of rice literature in the indexing, storage and speedy retrieval of information.
In the Categorized Listing, the terms are arranged hierarchically. The subject covers all aspects of rice production, divided into ten broad subject headings.
In the Alphabetical Listing, terms are arranged in alphabetical sequence word by word. There are 1045 preferred descriptors and 349 non-descriptors.
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Subject headings--Rice.; Thesauri